2020
DOI: 10.3389/fpsyg.2019.02772
|View full text |Cite
|
Sign up to set email alerts
|

They (Don’t) Need Us: Functional Indispensability Impacts Perceptions of Representativeness and Commitment When Lower-Status Groups Go Through an Intergroup Merger

Abstract: Intergroup changes occur often between subgroups who are asymmetric in status (e.g., size, power, prestige), with important consequences for social identification, especially among the members of lower-status groups. Mergers offer an example of such changes, when subgroups (merger partners) merge into a common, superordinate group (postmerger group). Lower-status subgroups frequently perceive they are less represented in the post-merger group, therefore committing less to the changes a merger implies. Five stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 83 publications
2
15
0
Order By: Relevance
“…Thus, it would seem highly promising to extend this research to field studies and also reexamine the moderating role of merger motive. In future research, our reasoning could be integrated with recent research on the functional indispensability of lower‐status groups involved in a merger (Rosa et al., 2019). As this research has shown, employees from a lower‐status group might cope more effectively with the merger threat when they view their ingroup as functionally indispensable.…”
Section: Limitations and Future Directionsmentioning
confidence: 93%
“…Thus, it would seem highly promising to extend this research to field studies and also reexamine the moderating role of merger motive. In future research, our reasoning could be integrated with recent research on the functional indispensability of lower‐status groups involved in a merger (Rosa et al., 2019). As this research has shown, employees from a lower‐status group might cope more effectively with the merger threat when they view their ingroup as functionally indispensable.…”
Section: Limitations and Future Directionsmentioning
confidence: 93%
“…Namely, for those who are members of low‐power groups and prospective members of a superordinate group, a sense of representativeness within the new group might be a necessary condition for mutually identifying with it and with one’s subgroup (see Sidanius et al., 2008). Research in the context of mergers finds representativeness to be a key driver of post‐merger identification with the superordinate group (Boen, Vanbeselaere, & Wostyn, 2010; Rosa et al., 2020), a relationship that might be mirrored in the context of EU integration. Our first research question for the quantitative study thus asks: How is supranational identification shaped by the perceived compatibility between sub‐ and superordinate groups, and what is the underlying role of power therein?…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that identity compatibility is key: When perceptions of identity compatibility were low, such that Serbia was perceived as relatively unrepresentative of Europe, the relationship between Serbian and European identity was negative. In contrast, when perceptions of compatibility were high, the relationship became positive, indicating that sense of representativeness can play an important role in making sub‐ and superordinate group identities mutually supportive (see Rosa et al., 2020). Identity compatibility was in turn predicted by the perceived current power of Serbia in Europe, and mediated the path between power in Europe and European identification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations